Different Levels of Exhaled Nasal Nitric Oxide in Patients Diagnosed with Primary Dyskinesia - A Bodini; D Peroni; L Tenero; M Sandri; M Brunelli; G Inzalaco; U Pradal; M Piazza; AL Boner; GL Piacentini (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2015)
Background: Primary ciliary dyskinesia (PCD) is a genetic disease characterized by abnormally beating cilia. In  these patients levels of nasal nitric oxide (nNO) are lower than those observed in healthy subjects.  Objectives: We recorded the nNO levels in PCD patients in order to use those nNO measurements in the screening and identification of patients with symptoms suggestive of disease PCD disease. Methods: We measured nasal NO in 36 PCD patients (3 uncooperative younger children and 33 cooperative adult patients) and did a nNO re-evaluation after 12 months in patients with higher levels of nNO. Results: Twenty-seven PCD patients showed very low nNO levels (29.1 ppb) and nine cooperative patients had high nNO levels (583.3 ppb, p<0.001) (T0); the PCD patients with high nNO levels were re-evaluated after 12 months (T1). The median T0 and T1 nNO values of the seven PCD patients were 360 ppb and 324  ppb(p=0.0180), respectively; in 6 patients with high levels of nNO the diagnosis of PCD was confirmed byelectron microscopy, and in one subject the diagnosis was confirmed for secondary ciliary dyskinesia. Conclusions: Low levels of  nNO remain  indicative of  PCD  disease; high levels of nNO are supportive of PCD, but cannot be used to exclude diagnosis.These results suggest that repeated measures are warranted when nNO is occasionally high inpatients with symptoms suggestive of PCD disease, and at present electron microscopy is still the only valid evaluation tool in unclear cases of PCD.